ANALISIS YURIDIS WANPRESTASI PERJANJIAN KERJA SAMA BAWAH TANGAN USAHA LAUNDRY DI KELURAHAN SEMOLOWARU SURABAYA - Salsabila, Lolita; Waluyo, Waluyo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This study aims to determine the form of agreement and construction of cooperation agreement under the hand of laundry business in Semolowaru Surabaya Village and to find out efforts to resolve the default of the cooperation agreement under the hands of laundry business in Semolowaru Surabaya Village. This research uses normative juridical methods by combining a statutory approach, a concept approach, an analytical approach, and a case approach. Data sources are obtained from interviews, legislation, books, scientific journals, and other literature. This research uses descriptive analytical research methods and data analysis using a qualitative approach. The results of the study can be concluded that the form of a laundry business cooperation agreement in Semolowaru Surabaya Village is an underhand agreement signed by both parties on stamp duty (without the involvement of general officials). However, in the cooperation agreement under the hands of the laundry business in Semolowaru Village, Surabaya, there are some that are not in accordance with the provisions of the composition and anatomy of an agreement in general, namely there are no witnesses and no attachments. And efforts to resolve defaults on the cooperation agreement under the hands of the laundry business in Semolowaru Surabaya Village that have been carried out by the parties, namely by non-litigation settlement efforts or by negotiation between the two parties through deliberation, but were unsuccessful and did not go well